Who’s the Man – Masculinties Studies, Terry Stops, and Police Training - Cooper, Frank Rudy (Columbia Journal of Gender and Law, 2009)
We men have some strange rituals. One occurs on the basketball court. A player will make a move around a defender and score a basket. Then he’ll shout, “who’s the man?” He wants his opponent to say, “You are the man.” This episode is a paradigmatic description of how masculinities work. Men often act with the goal of impressing other men. We gain our masculine esteem and relative masculine stature from other men’s acknowledgements of our masculinity. Sociologist Michael Kimmel puts it best: “[w]e are under the constant careful scrutiny of other men. Other men watch us, rank us, grant our acceptance into the realm of manhood. Manhood is demonstrated for other men’s approval.” The need for other men’s approval leads us to constantly call out, “who’s the man?.” Kimmel helps us see that masculinities are expressed through encounters where one man can demand that another man acknowledge him as “the man.” The existence of the “who’s the man?” game is revealed by studying hegemonic masculinity5 using the literature from the field of masculinities studies. To date, the legal literature on masculinities has focused on employment discrimination and equal protection. This Article applies the masculinities studies literature to the field of criminal procedure and asks the following question: How does masculinity affect policing? This is an important question, given that policemen have nearly unique powers to make others acknowledge them as “the man” while ostensibly merely performing their duties.